Evaluasi Pelaksanaan Program Pencegahan Stunting: Literature Review - Julia Fakhrun Nisa; Sri Sumarmi (Universitas Airlangga, 2024)
Background: Stunting is one of the major health issues resulting from chronic malnutrition that continues to be a priority for the government to address urgently. The implementation of stunting prevention programs has been ongoing across various regions in Indonesia for a considerable time. It is essential to monitor and evaluate these programs to determine whether they are currently running smoothly or not. Objectives: This study aims to assess the extent of government efforts in addressing the stunting problem and to evaluate the programs that have previously been and are currently being implemented comprehensively across Indonesia. Methods: : The researchers employed a literature review approach by collecting and reviewing previous studies on the evaluation of stunting programs from the Google Scholar database, covering the years 2019-2023. A total of 8 articles evaluating the implementation of stunting programs were analyzed, focusing on components such as input, process, and output. Results: This study reveals that in terms of input, the evaluation found limitations in funding, human resources, implementation procedures, and infrastructure. Evaluation of the process aspect involved planning, organization, actualization, and reporting of program implementation. The output aspect was reviewed based on the achievement of program success indicators. Conclusions: Based on the evaluation of the stunting prevention programs in terms of input, process, and output, it was found that the programs have been well-implemented in some health centers or regions. However, several obstacles were also encountered.